ChemInform Abstract: A General and Highly Selective Method for the Asymmetric Synthesis of Trifluoromethyl‐Substituted α‐ and β‐Aminophosphonates. Issue 7 (18th February 2014) - Wang, Lijing; Shen, Qilong; Lu, Long
Abstract The synthesis of a variety of α‐aminophosphonates employing enantiopure N‐tert‐butanesulfinylimine as auxiliary is described.